Komplet udgave i en fil - Hopmann, David Nicolas (Journalistica - Tidsskrift for forskning i journalistik, 1970)
Komplet udgave i en fil
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuNzE0Ni9qb3VybmFsaXN0aWNhLnY0aTIuMzgzOQ